Service Optimization, Incentive Systems, and Social Media Digitalization: Their Impact on Waste Bank Programs through Community Participation - Fira Eryani; Amri Amri; Yulianti Yulianti; Hidayat Febiansyah (Jurnal Multidisiplin Sahombu, 2026)
This study examines how community participation mediates the influence of service quality, incentive systems, and social media on the impact of Waste Bank programs in the Bangka Belitung Islands. A quantitative method with explanatory design was employed with 83 active customer respondents. PLS-SEM analysis was utilized to test seven hypotheses. The results demonstrated that service quality positively influenced community participation with a coefficient of 0.368 (p < 0.001). The incentive system also promoted participation with a coefficient of 0.297 (p < 0.001). Social media exhibited the strongest influence with a coefficient of 0.432 (p < 0.001). Community participation subsequently exerted a very strong influence on program impact with a coefficient of 0.736 (p < 0.001). All three independent variables also demonstrated indirect effects on program impact through participation with coefficients of 0.271, 0.219, and 0.318 respectively. The model explained 62.3% of variance in participation and 54.7% of variance in program impact. These findings suggest the importance of integrating responsive service, varied incentives, and digital platforms to enhance participation. A 10% increase in service quality can enhance participation by 3.7% and consequently increase program impact by 2.7%. Waste Bank managers need to prioritize social media optimization as it exhibits the greatest influence, followed by service and incentive systems.